Ringing in the 20th Century : The Effects of State Monopolies, Private Ownership, and Operating Licenses on Telecommunications in Europe, 1892-1914 - Wallsten, Scott (World Bank, Washington, DC, 2014)
Countries around the world are liberalizing their telecommunications networks by privatizing incumbent state-owned firms and introducing competition. For many, this change represents a return to private provision and competition-not a new phenomenon. The beginning of the 20th century saw great variation in the structure of telecommunications sectors, with some countries operating state monopolies and others-especially in Scandinavia-allowing vigorous private competition. The author uses data on countries around the world in 1913 and on European countries in 1892-1914 to test the effects of government monopolies, private provision, and operating licenses on telephone development. Controlling for per capita income and, where possible, for country and year fixed effects, he finds that state monopoly provision is correlated with substantially lower telephone penetration and higher consumer prices for long-distance service than private provision. Contrary to conventional wisdom, rural service was also worse under state-owned monopolies. Operating licenses that gave the state the right to appropriate firms' assets similarly led to lower telephone penetration and higher prices.